AMAZON’S DIGITAL LOCAL MEDIA COVERAGE ON LARGE DEVELOPMENT PROJECTS WITH SOCIO-ENVIRONMENTAL IMPACT - Gomes Salles, Débora; Santos, Marina Loureiro; Monteiro Albuquerque de Magalhães, Thamyres; Melo, Bianca Maria da Silva; Dias, Julia Santos Rodrigues; Sanchotene, Nicole; Santini, Rose Marie (AoIR Selected Papers of Internet Research, 2026)
Brazil plays a key geopolitical role in global environmental decisions. However, large development projects linked to agribusiness and mining are often promoted under developmentalist rhetoric despite their socio-environmental controversies. In the Amazon, where these projects are concentrated, digital local media serves as a platform for political and economic interests. While other studies highlight local journalism’s role in diversifying news perspectives, Brazil’s case differs due to financial constraints, political influence, and content reproduction. This research examines how digital local media in the Amazon reports on four large development projects: the resurfacing of the BR-319 highway, the construction of the Ferrogrão railway, oil drilling at the mouth of the Amazon River, and potassium extraction on Indigenous lands. Using systematic content analysis, we assessed 3,555 articles published by 186 outlets, identifying the positioning of the outlets, actor representation, geographical scales of impact or benefit mentioned, and content reproduction. Findings reveal that digital local media largely supports large development projects, emphasizing the national scale and economic growth over socio-environmental concerns. In articles opposing the projects, mentions of local impacts stand out. The study also shows that 65.2% of the articles were republished, mostly from news agencies, reinforcing content homogenization. Local politicians and agribusiness representatives dominate coverage, while affected communities and environmental voices remain marginalized. This research highlights how local media in the Amazon amplifies elite narratives, neglecting environmental issues. It underscores the journalistic fragility of the region and the urgent need for stronger, independent environmental journalism.